Implications of noncoding RNAs for cancer therapy: Are we aiming at the right targets? - Amil Shah (Exploration of Targeted Anti-tumor Therapy)
The discovery of oncogenes and tumor suppressor genes led to a better understanding of tumorigenesis, and prompted the development of molecularly targeted therapy. Over the past 30 years, many new drugs, which are primarily aimed at activated oncogenic proteins in signal transduction pathways involved in cell proliferation and survival, have been introduced in the clinic. Despite its rational design, the overall efficacy of targeted therapy has been modest. Recently, the noncoding RNAs (ncRNAs) have emerged as key regulators of important cellular processes in addition to the known regulatory proteins. It now appears that dual epigenetic regulatory systems exist in higher eukaryotic cells: a ncRNA network that governs essential cell functions, like cell fate decision and maintenance of homeostasis, and a protein-based system that presides over core physiological processes, like cell division and genomic maintenance. Modifications of the ncRNA network due to altered ncRNAs can cause the cell to shift towards to neoplastic phenotype; this is cancer initiation. Mutations in the well-known cancer driver genes provide the incipient cancer cell with a selective growth advantage and fuel its consequent clonal expansion. Because of the crucial role of the altered ncRNAs in tumorigenesis, targeting them may be a reasonable therapeutic strategy.